2020
DOI: 10.1021/acs.jmedchem.9b01549
|View full text |Cite|
|
Sign up to set email alerts
|

Unique Sulfur–Aromatic Interactions Contribute to the Binding of Potent Imidazothiazole Indoleamine 2,3-Dioxygenase Inhibitors

Abstract: Indoleamine 2,3-dioxygenase (IDO1) inhibitors are speculated to be useful in cancer immunotherapy, but a phase III clinical trial of the most advanced IDO1 inhibitor, epacadostat, did not meet its primary end point and was abandoned. In previous work, we identified the novel IDO1 inhibitor N-(4-chlorophenyl)-2-((5-phenylthiazolo­[2,3-c]­[1,2,4]­triazol-3-yl)­thio)­acetamide 1 through high-throughput screening (HTS). Herein, we report a structure–activity relationship (SAR) study of this compound, which resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…4). 13 Figure 4 shows hits targeting ANAT (15)(16)(17)(18)(19) identified in a virtual screen using AtomNet, a deep convolutional neural network for structure-based drug discovery. In this case, the authors provided high-performance liquid chromatography-mass spectrometry (HPLC/MS) confirmation of their hits [purity/ id = good]; the hits were predicted to be non-promiscuous [promiscuity = good] by Hit Dexter but received warnings and cautions when analyzed in Badapple.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). 13 Figure 4 shows hits targeting ANAT (15)(16)(17)(18)(19) identified in a virtual screen using AtomNet, a deep convolutional neural network for structure-based drug discovery. In this case, the authors provided high-performance liquid chromatography-mass spectrometry (HPLC/MS) confirmation of their hits [purity/ id = good]; the hits were predicted to be non-promiscuous [promiscuity = good] by Hit Dexter but received warnings and cautions when analyzed in Badapple.…”
Section: Resultsmentioning
confidence: 99%
“…Of these compounds, the NHV warns of potential promiscuity for 22 17 and 23 , 18 which would need to be de-risked in the screening tree. Compound 26 19 has a warning in [tiering], suggesting that the physicochemical properties of this hit may need to be optimized on the way to becoming an effective probe or drug candidate. Compound 25 20 is relatively free of warnings and appears to be an excellent starting point given its [tiering] value.…”
Section: Resultsmentioning
confidence: 99%
“…Some similarities (shape, planes) are found with known ligands of IDO1, particularly D09, PKJ and DYC from 4PK5 (chain A), 6KOF (chain A) and 6KW7 (chain A) respectively. 27,28 These protein structures are classified in the same cluster than 5EK2a used for the docking studies. The pattern of interactions is different from the one of 5, with more involvement of Pi (cycles, cations, sulfur) interactions.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…In these trials, Epacadostat showed significant regression to melanoma, head, and neck, lung, renal and urothelial cancers [26a,37,44] when co‐administered with checkpoint inhibitors. But, when Epacadostat entered Phase III clinical trials, [45] it failed to induce significant survival in patients with stage III and IV melanoma [38,46] …”
Section: Discovery Of the Clinical Candidates Of Selective Hido1 Inhibitors And The Scheme Of Binding Inhibition Into The Enzyme Active Smentioning
confidence: 99%